Changes in physical and technical match performance variables in football players promoted from the Spanish second division to the first division - Ferrandis, J.; Coso, J.; Moreno-Pérez, V.; López-Del Campo, R.; Resta, R.; González-Rodenas, J. (Biology of Sport, 2024)
The aim of this study was to compare physical and technical match performance variables in football players who competed in the Spanish second division for one season and were promoted to the top (first) division in the following season. A total of 97 male outfield football players who were promoted from the second to the first division of the Spanish professional football league within the same team were analysed. Data were recorded using the TRACAB (ChyronHego, New York, USA) multicamera computerised optical tracking system during five seasons (2015-2016 to 2019-2020). A one-way ANOVA repeated measures analysis showed that players executed a greater number of high-intensity running (HIR) efforts (P < 0.001; ES: 0.258), as well as covering greater HIR distance (P < 0.010; ES: 0.106) and total running distance (TD) (P < 0.010; ES: 0.080), when they played in the first division compared with the second division. Moreover, players performed a lower number of passes (P < 0.01; ES = 0.116), short passes (P < 0.01; ES = 0.106), long passes (P < 0.05; ES = 0.067), dribbles (P < 0.001; ES = 0.146) and shots (P < 0.01; ES = 0.074) in the first division compared to the second division. No significant differences were found for any of the defensive variables evaluated. In conclusion, being promoted from the second to the first division of professional football requires players to adapt to greater physical demands and a reduced number of technical actions.